1998
DOI: 10.1111/j.1540-8159.1998.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pulsed‐Doppler Tissue Imaging in Patients with Dual Chamber Pacing: The Importance of Conduction Time and AV Delay on Regional Left Ventricular Wall Dynamics

Abstract: The noninvasive measurement of timings of the cardiac cycle by pDTI is helpful to determine the optimal AVD in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1 -6 Previous articles outlined the in uence exerted by heart rate (HR) and atrioventricular delay (AVD) changes on left ventricular (LV) diastolic lling patterns in patients with dualchamber pacemakers. [7][8][9][10][11][12][13][14][15] However, right ventricular (RV) adaptation to DDD pacing has not been investigated satisfactorily. RV geometry and morphology differ consistently from LV geometry and morphology such that during dualchamber stimulation, its diastolic lling pattern might result differently as affected by DDD pacing.…”
mentioning
confidence: 99%
“…1 -6 Previous articles outlined the in uence exerted by heart rate (HR) and atrioventricular delay (AVD) changes on left ventricular (LV) diastolic lling patterns in patients with dualchamber pacemakers. [7][8][9][10][11][12][13][14][15] However, right ventricular (RV) adaptation to DDD pacing has not been investigated satisfactorily. RV geometry and morphology differ consistently from LV geometry and morphology such that during dualchamber stimulation, its diastolic lling pattern might result differently as affected by DDD pacing.…”
mentioning
confidence: 99%
“…Previous studies have shown that electrical conduction pathways are variable from patient to patient, such that the latest and earliest activation is not always observed at the LV free wall and septum, respectively. 15,16 Similarly, this study has shown that the latest and earliest activating sites along a quadripolar lead vary widely among patients, regardless of the source of the activation wavefront. While the most proximal LV electrode (P4) was most commonly the latest activating and the most distal LV electrode (D1) was most commonly the earliest activating during both conduction types, all four electrodes exhibited latest and earliest activations in this patient population.…”
Section: Spatial Differences In Conduction Pathways With Versus Withoutmentioning
confidence: 58%